Cover Picture: ChemMedChem has reached…︁The Big TEN! (ChemMedChem 1/2015). Issue 1 (January 2015) - Williams, Scott D.; Ortúzar, Natalia
<x xml:space="preserve">Abstract</x> Celebrating Volume 10! The inaugural issue of ChemMedChem was published in January 2006, and since then the journal has gone from strength to strength. Over the last nine years, ChemMedChem has continually attracted high‐caliber authors, and the readership has steadily grown thanks to the journal's high scientific and production standards. This success would not have been possible without committed board members, dedicated peer reviewers, excellent authors, and enthusiastic readers—thanks to all of you for your continued support. Now with volume numbers in double digits, ChemMedChem can truly be considered an established journal in medicinal chemistry. For more insight into ChemMedChem's growth and development, see the Editorial on p. 11 ff.<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>